Familial association of pseudohypoparathyroidism and psoriasis: case report - Montenegro Junior, Renan Magalhães; Paula, Francisco José Albuquerque de; Foss, Norma Tiraboshi; Foss, Milton Cesar (São Paulo Medical Journal, 2002)
CONTEXT: The association between psoriasis and hypoparathyroidismhasbeenreportedbyseveral authors, and it has been suggested that abnormalities in calcium homeostasis may be involved in the development or exacerbation of psoriasis. However, so far there have only been two reports of pseudohypoparathyroidism associated with psoriasis. OBJECTIVE: To describe the familial occurrence of this association for the first time. CASE REPORTS: Two siblings with psoriasis associated with pseudo hypoparathyroidism we represented. Thefirstpatientwasa24-year-oldwhitemalewith disseminated erythro dermic pustular psoriasisthat began2months before admission. He had hada history of mental retardation, recurrentotitis, seizures and arthralgiafromthe age of 11 years on wards. He presented the characteristic phenotype of Albright osteodystrophy: short stature, obesity, roundfacies, broad fore head, short neck and brachy dactylia. He adopted a position of flexed limbs and showed proximal muscle weak nessanda positive Trousseau sign. He had clinical signs of hypocalcemia (0.69 mmol/l ionized calcium and 3.2 mg/dl total calcium), hyperphosphatemia (6.6 mg/dl), hypomagnesemia(1.0mEq/l), hypoalbuminemia (3.1 g/dl), normal serum intact PTH levels (45.1 pg/ml), primaryhy pothyroidism (13.2mU/mlTSH, and 4.7 mg/dl total T4), hypergonadotrophic hypogonadism(116.0ng/mlLH,13.2mU/mlFSH and 325.0 ng/dl testosterone), osteoporosis, and diffuse calcification sinsof ttissue sand in the central nervous system. The second case was a 14-year- old white girl with a history of psoriasis vulgaris from the age of five years on wards,and antecedents of mental retardation. She presented signs of Albright osteodystrophy (shortstature, roundfacies, obesity, short neck, brachydactylia),hypocalcemia (ionized calcium of 1.08 mmol/l and total calcium of 6.7 mg/dl) hyperphosphatemia (9.4mg/dl),elevated serum PTH levels(223.0pg/ml), osteoporosis, and hyper gonadotrophic hypogonadism (7.0mU/mlLH, 9.3mU/mlFS Hand undetectable estradiol levels).